7(y-4)=9y-40

Simple and best practice solution for 7(y-4)=9y-40 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(y-4)=9y-40 equation:


Simplifying
7(y + -4) = 9y + -40

Reorder the terms:
7(-4 + y) = 9y + -40
(-4 * 7 + y * 7) = 9y + -40
(-28 + 7y) = 9y + -40

Reorder the terms:
-28 + 7y = -40 + 9y

Solving
-28 + 7y = -40 + 9y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-9y' to each side of the equation.
-28 + 7y + -9y = -40 + 9y + -9y

Combine like terms: 7y + -9y = -2y
-28 + -2y = -40 + 9y + -9y

Combine like terms: 9y + -9y = 0
-28 + -2y = -40 + 0
-28 + -2y = -40

Add '28' to each side of the equation.
-28 + 28 + -2y = -40 + 28

Combine like terms: -28 + 28 = 0
0 + -2y = -40 + 28
-2y = -40 + 28

Combine like terms: -40 + 28 = -12
-2y = -12

Divide each side by '-2'.
y = 6

Simplifying
y = 6

See similar equations:

| x/5x-40*x*x-8x/7= | | 3(4x+1)=9(2x-1) | | -6n(1+10n)= | | 0=11x-3x^2-10 | | -43=6b+8 | | 125m-100m+38800=40200-175m | | -6(x+3)-12=17+7 | | 1.39=ln(y) | | 6a^2-a-15= | | 2y+1y+15=22 | | 6x=16-x^2 | | 1/3(3.14)(3.5^2)8 | | 6y+2-7y= | | 18-9b=-b^2 | | -14=2(u+8)-7u | | -11u--6u-2u-8=20 | | f(x)=12x-x^3 | | 6.9x-2.1=25.5 | | y-17/19=-719 | | 3k-1-6k=4k+8-9k | | 7x+26=5x+56 | | 2m^2=-7m | | -14=3(x-8)-8x | | C^2-13c+40= | | 8(w+4)-5w=20 | | -12x+5y=60 | | 4-.4x=.2x-8 | | 3x(2x+4)=6(5x+2) | | 8w+3-10w= | | 2w-11w=-12 | | 7.9=2n-5 | | y+y+x+39=180 |

Equations solver categories